BREAKING THE MOULD: A CASE STUDY OF A DIGITAL LEARNING COMMONS IMPLEMENTATION PROJECT - Van Wyk, B; Kadzenga, I (My University, 2016)
One of the four brands of a South African higher education institution implemented its first digitally enabled campus in Polokwane, South Africa during 2015, opening its doors to new cohorts for the first time in January 2016. This new Rosebank College campus changed the tertiary landscape by embarking on a different model of education, offering all teaching and learning, as well as support services, in a digitally enabled environment. From a focus on e-learning via the Blackboard Learn Management System (LMS), supported by a number of scheduled contact sessions, to digital library services this digitally enabled campus was designed to cater for a new mode of delivery. In order to cater for the information needs of the new campus, a digital library and information service (LIS) model was required as opposed to the traditional paper-based library service. This new approach is changing the landscape of information services. Valuable lessons were learnt during the planning and implementation of the digital learning commons. In this paper, an overview is provided of how it was planned and implemented, and lessons learnt are shared.
Keywords: Digital Learning Commons; Private Higher Education; Academic Libraries